Thiazolyl-pyrazole derivatives as potential antimycobacterial agents - Takate, Sushma J.; Shinde, Abhijit D.; Karale, Bhausaheb K.; Akolkar, Hemant; Nawale, Laxman; Sarkar, Dhiman; Mhaske, Pravin C. (Bioorganic & Medicinal Chemistry Letters, 2019)
Mycobacterium tuberculosis (Mtb) is an obligate aerobe that is capable of long-term persistence under conditions of low oxygen tension. A series of thiazolyl-pyrazole derivatives (6a-f, 7a-f, 8c, 8e) were screened for antimycobacterial activity against dormant M. tuberculosis H37Ra (D-MTB) and M. bovis BCG (D-BCG). Nine thiazolyl- pyrazole analogs, 6c, 6e, 7a, 7b, 7c, 7e, 7f, 8c and 8e exhibited promissing minimum inhibitory concentration (MIC) values (0.20-28.25 mu g/mL) against D-MTB and D-BCG strains of Mtb. Importantly, six compounds (7a, 7b, 7e, 7f, 8c and 8e) exhibited excellent antimycobacterial activity and low cytotoxicity at the maximum evaluated concentration of > 250 mu g/mL. Finally, the promising antimycobacterial activity and lower cytotoxicity profile suggested that, these compounds could be further subjected for optimization and development as a lead, which could have the potential to treat tuberculosis.
Keywords: antimycobacterial activity; Cytotoxicity; Pyrazole; thiazoles

Synthesis of new thiazole and pyrazole clubbed 1,2,3-triazol derivatives as potential antimycobacterial and antibacterial agents - Jagadale, Shivaji M.; Abhale, Yogita K.; Pawar, Hari R.; Shinde, Abhijit; Bobade, Vivek D.; Chavan, Abhijit P.; Sarkar, Dhiman; Mhaske, Pravin C. (Polycyclic Aromatic Compounds, 2022)
New series of 4-methyl-2-(4-substituted phenyl)-5-(4-((4-(4-substituted phenyl)-1H-1,2,3-triazol-1-yl)methyl)-1-phenyl-1H-pyrazol-3-yl)thiazole, 6a-t and 4-(1,3-diphenyl-1H-pyrazol-4-yl)-1-((1,3-diphenyl-1H-pyrazol-4-yl)methyl )-1H-1,2,3-triazole, 11a-o derivatives have been synthesized by applying copper-catalyzed [3 + 2] cycloaddition reaction. The newly synthesized 1,3-thiazolyl-pyrazolyl-1,2,3-triazole (6a-t) and bis-pyrazolyl-1,2,3-triazole (11a-o) derivatives were screened for in vitro antimycobacterial activity against M. Tuberculosis H37Ra dormant and active and antibacterial activity against four pathogenic bacteria, E. coli (NCIM 2576), P. flurescence (NCIM 2059), S. aureus (NCIM 2602) and B. subtilis (NCIM 2162). Compounds 6a, 6f, 6j, 11e and 11m showed good activity against M tuberculosis H37Ra Active strain, also compounds 6g, 6h, 11f, 11n and 11o showed good activity against M tuberculosis H37Ra Dormant strain. Compounds 6b, 6i, 6l, 6o, 6r, 11k, 11l and 11m showed good activity against B. subtilis with IC50 1.99-2.96 mu g/mL. The antibacterial activity of thiazolyl-pyrazolyl-1,2,3-triazole and bis-pyrazolyl-1,2,3-triazole derivatives suggested that, these derivatives could lead to new compounds for treatment against bacterial infection.
Keywords: 123-Triazole; antibacterial activity; antimycobacterial activity; Pyrazole; Thiazole